Sedentary Lifestyle and Overweight in Relation to the Risk of Polycystic Ovary Syndrome in Senior High School Students in Surabaya - Shafira Noorania Putri; Budi Santoso; Budiono Budiono (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Highlights:1. Most senior high school students live a sedentary lifestyle.2. Hyperinsulinemia and hyperandrogenism were related to an increased risk of PCOS in adolescents.3. Sedentary lifestyle and overweight were found to have a significant correlation with increased risk of PCOS in adolescents. AbstractIntroduction: Adolescent polycystic ovary syndrome (PCOS) is one of the endocrine and metabolic disorders characterized by oligomenorrhea and hyperandrogenism. A sedentary lifestyle in adolescence increases the risk of overweight and obesity. Being overweight may increase the risk of PCOS in adolescents by the mechanism of insulin resistance and hyperinsulinemia, which affects the function of adrenal and ovarium androgen production. The increase of androgen has an important effect on PCOS. This study aimed to examine the relationship between a sedentary lifestyle and being overweight as the risk of PCOS in adolescents.Methods: This was an observational analytic study with a cross-sectional design. This study was held at State Senior High School (SMAN) 5 Surabaya from February to April 2020. The sample of this research was chosen by random sampling of all female students in SMAN 5 Surabaya. The data were collected by direct measurement of student’s weight and height and a questionnaire consisting of Global Physical Activities Questionnaire, menstrual cycle, and Ferriman–Gallwey score. The students were stated at risk of PCOS if they had an abnormal uterine bleeding pattern and had Ferriman–Gallwey score ≥5. The data were analyzed using logistic regression analysis.Results: Of 82 students (100%), 32 students were overweight (39%), 5 students had obesity (6.1%), 44 students were performing a sedentary lifestyle (53.7%), 42 students had Ferriman–Gallwey score ≥5 (51.2%), 38 students had an abnormal uterine bleeding pattern (43.3%), and 35 students were at risk of PCOS (42.6%). Logistic regression analysis showed there was a significant relationship between a sedentary lifestyle and the risk of PCOS (p = 0.004) and a significant relationship between being overweight and the risk of PCOS (p < 0.001). People with a sedentary lifestyle have 6.3 folds higher risk of PCOS than normal people, and people with overweight have 16.2 folds higher risk of PCOS than normal people.Conclusion: Sedentary lifestyle and overweight have the role of increasing the risk of PCOS in adolescents.